PROBLEMS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE TO STUDENTS IN UZBEKISTAN - Turaeva Shahida Egamberdievna (American Journals, 2023)
The article discusses the main difficulties that arise when teaching technical students at the first course, for whom native language - Uzbek. Knowledge of distinctive features of the phonetic system and morphology of the Uzbek language allows to select the right exercises and properly organize learning activities in the classroom for Russian as a foreign language. Also important is training the official and scientific styles of speech, as well as the formation of skills of production monologic statement.
Keywords: Phonetic interference, category of a sort, spelling literacy, culture of speech activity, communicative competence.